Can We Finish the Revolution? Gender, Work-Family Ideals, and Institutional Constraint - Pedulla, David S.; Thébaud, Sarah (American Sociological Review, 2015)
Why has progress toward gender equality in the workplace and at home stalled in recent decades? A growing body of scholarship suggests that persistently gendered workplace norms and policies limit men’s and women’s ability to create gender egalitarian relationships at home. In this article, we build on and extend prior research by examining the extent to which institutional constraints, including workplace policies, affect young, unmarried men’s and women’s preferences for their future work-family arrangements. We also examine how these effects vary across education levels. Drawing on original survey-experimental data, we ask respondents how they would like to structure their future relationships while experimentally manipulating the degree of institutional constraint under which they state their preferences. Two clear patterns emerge. First, as constraints are removed and men and women can opt for an egalitarian relationship, the majority choose this option, regardless of gender or education level. Second, women’s relationship structure preferences are more responsive than men’s to the removal of institutional constraints through supportive work-family policy interventions. These findings shed light on important questions about the role of institutions in shaping work-family preferences, underscoring the notion that seemingly gender-traditional work-family decisions are largely contingent on the constraints of current workplaces.